2006
DOI: 10.1074/jbc.m600496200
|View full text |Cite
|
Sign up to set email alerts
|

The P174L Mutation in Human Sco1 Severely Compromises Cox17-dependent Metallation but Does Not Impair Copper Binding

Abstract: Sco1 is a metallochaperone that is required for copper delivery to the Cu A site in the CoxII subunit of cytochrome c oxidase. The only known missense mutation in human Sco1, a P174L substitution in the copper-binding domain, is associated with a fatal neonatal hepatopathy; however, the molecular basis for dysfunction of the protein is unknown. Immortalized fibroblasts from a SCO1 patient show a severe deficiency in cytochrome c oxidase activity that was partially rescued by overexpression of P174L Sco1. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…The essential requirement of two Sco proteins in humans is therefore accounted for by these different, specific functions. Notably, both human Sco proteins are active in their copper-bound forms, accounting for the observation that mutation of any of the copper ligands severely affects the oxidase activity and cellular respiration (40,41). The most frequent pathological mutations (P174L in Sco1 and E140K in Sco2) are located close to the CX 3 CX n H motif, and thus expected to alter either the copper-binding or the redox capabilities of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The essential requirement of two Sco proteins in humans is therefore accounted for by these different, specific functions. Notably, both human Sco proteins are active in their copper-bound forms, accounting for the observation that mutation of any of the copper ligands severely affects the oxidase activity and cellular respiration (40,41). The most frequent pathological mutations (P174L in Sco1 and E140K in Sco2) are located close to the CX 3 CX n H motif, and thus expected to alter either the copper-binding or the redox capabilities of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular defect in the P174L mutant Sco1 is an impaired ability to be copper metallated by Cox17 (7,20). The defect is attributed to an attenuated interaction with Cox17 (20), in addition to a modest structural defect that attenuates the Cu(I) binding affinity (7). Defective Cox17-mediated copper metallation of Sco1, and subsequent failure of Cu A site maturation, is the basis for the inefficient assembly of the CcO complex in SCO1 patient fibroblasts.…”
mentioning
confidence: 99%
“…The P174L substitution is adjacent to the second Cys in the Cu(I)-binding CX 3 C motif in Sco1, yet the mutant protein retains the ability to bind Cu(I) or Cu(II) when expressed in bacteria. The molecular defect in the P174L mutant Sco1 is an impaired ability to be copper metallated by Cox17 (7,20). The defect is attributed to an attenuated interaction with Cox17 (20), in addition to a modest structural defect that attenuates the Cu(I) binding affinity (7).…”
mentioning
confidence: 99%
“…One copper atom is bound per monomer, and mutations that impair Cu(I) or Cu(II) binding result in a non-functional SCO protein, arguing that this property is crucial to their roles in COX assembly (71). The importance of copper binding to SCO1 function is emphasized by two parallel studies that both found the pathogenic P174L substitution in SCO1 severely compromises COX17-dependent copper transfer (72,73). Whether mutations in SCO2 also impair copper transfer from COX17 remains unclear.…”
Section: Coa6 Sco1 and Sco2 Form A Metallochaperone Module That Intementioning
confidence: 85%
“…Mutations in residues within this loop 8 motif do not affect physical interactions with Cox17 or copper-binding, arguing that Sco1 uses distinct interfaces to interact with Cox17 and Cox2 (76). Pulse-chase labeling of mitochondrial translation products in human cells established that impaired SCO1 function did not affect COX2 synthesis but resulted in accelerated turnover of the newly synthesized protein (73). In contrast, COX2 synthesis is greatly reduced in SCO2 patient cells, yet the residual protein that is made is much more stable than in control cells (31).…”
Section: Coa6 Sco1 and Sco2 Form A Metallochaperone Module That Intementioning
confidence: 99%